Rhetorical Language Style in Benron Taikai ｢弁論大会｣ Manuscripts - Sri Wahyu Widiati; aulia, rahma; Nana Rahayu (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
The research entitled Rhetorical Language Style in Benron Taikai Manuscripts ｢｣ aims to describe the rhetorical language style of speech texts of exchange students in the benron taikai ｢｣competition. from 2019 there were 3 speech manuscripts and in 2021 there were 2 speech manuscripts. This research is descriptive qualitative in nature. The data source in this study used transcripts of benron taikai’s ｢｣ speech texts. The theory used in this research is the theory of rhetorical language style studies according to Gorys Keraf (2007). The data collection methods and techniques used in this research were listening methods and note-taking techniques. The results of this research are rhetorical language styles which found 17 speech quotations in the form of asyndetonal rhetorical language style 「アシンデトン」3 speech quotations, euphemism rhetorical language style ｢｣ 3 utterances, erotic rhetorical language style or rhetorical statements ｢ 的疑問法(てきぎもんほう)｣ 10 speech and rhetorical styles of zeugma ｢くびき｣ 1 speech quote.